The mysterious power of Xing Yi Quan : a complete guide to history, weapons and fighting skills - Tang, C. S. (Singing Dragon, 2013)
This in-depth, fully-illustrated guide covers the history and traditions of this Chinese martial art, describing its movements, and their effects. It contains a full teaching guide to this potent fighting system and its underlying principles, including the Twelve Animal Forms, linking forms, two person sets, basic skills and weapons training.